Study of the Performances of A Supply-Air Window for Air Renewal Pre-Heating. (November 2015) - Gloriant, François; Tittelein, Pierre; Joulin, Annabelle; Lassue, Stéphane
Abstract: The principle of a supply-air window is based on the air renewal circulation between the glazings of a window before entering home. We study in this work the Paziaud ® window composed of three glazings forming a U-shaped channel. The air warms up by recovering some part of the heat losses from the building and also by solar radiation absorbed through the glasses. This system generally works in forced convection by association with an air extraction system. This type of component is not embedded in usual dynamic tools for building thermal simulation. A major reason of this lack is that the heat transfers through the walls and the air exchange are treated separately. Moreover, this particular system is characterized by different heat fluxes if we consider the inner or the outer surface of the component. Our contribution is based on an original and appropriate representation of convective heat transfer in asymmetrically heated air layers. We offer a "simplified" model that can be easily implemented in dynamic simulation tools. This model is compared CFD simulations. From this model, parametric studies are performed to look for the parameters influencing the performance of the Paziaud® window: we show here that boundary conditions in temperatures, the thickness of the cavities, low emissivity coatings and the glazing area have significant effects on the performance criteria. We perform the parametric study on the basis of indicators specifically defined for the supply-air window.